The Effectiveness of Digital Learning Media on Students' Understanding of Science Concepts: A Literature Review (2013–2022) - Lalu Azikri Amrullah; Irman Muliadi; Ahmad Hardyan Isnaini; Shelliana Iqlima; Neli Yuliani; Windy Zaerani; Nurmayanti Nurmayanti (Indonesian, 2023)
The fundamental understanding of science concepts is often hindered by the abstract, microscopic, and complex characteristics of science topics. This study aims to map, classify, and evaluate the effectiveness trends of using digital-based learning media on improving students' science concept understanding. The method employed was a Systematic Literature Review (SLR) by analyzing 10 core articles published between 2013 and 2022, retrieved from Google Scholar, SINTA, and Portal Garuda databases. The results indicated that the integration of digital learning media consistently contributes significantly to reducing misconceptions and strengthening students' cognitive structures through three main media characteristics. First, interactive multimedia and digital simulations successfully reduce students' cognitive load through a multimodal approach. Second, self-directed digital teaching materials such as e-modules effectively facilitate self-regulated learning. Third, audiovisual media and recreational elements (educational games and digital comics) stimulate intrinsic motivation, resulting in strong concept retention in long-term memory. In conclusion, the success of strengthening science concepts in the digital era highly depends on the strategic alignment between the design of media characteristics and the instructional needs of the learners.